Association between Metrnl and carotid atherosclerosis in patients with type 2 diabetes mellitus - Li, Chunmei; Huang, Qiongzhu; Zhuang, Yanqian; Chen, Pin; Lin, Yiyang (Frontiers in Endocrinology, 2025)
ObjectiveType 2 diabetes mellitus (T2DM) is a major cause of atherosclerosis, as well as an independent risk factor of cardiovascular adverse events. We aimed to evaluate the association of serum Meteorin-like protein (Metrnl) level with carotid atherosclerosis as determined by carotid intima-media thickness (CIMT) status in subjects with T2DM.MethodsThis cross-sectional study included 83 T2DM subjects without pre-existing cardiovascular diseases. CIMT was measured by color doppler ultrasonography, while serum Metrnl level was measured by Enzyme-linked Immunosorbent Assay (ELISA) assay. According to the CIMT status, the subjects were divided into two groups: T2DM without atherosclerosis (DM-AS, CIMT<1.0mm) and T2DM with atherosclerosis (DM+AS, CIMT ≥1.0mm or carotid plaque).ResultsSerum Metrnl level was significantly increased in DM+AS group as compared to DM-AS group (0.77 ± 0.24 vs 0.51 ± 0.28 ng/ml, P <0.05). Binary logistic regression analysis showed that T2DM subjects in the fourth quartile of Metrnl levels demonstrated significantly higher risk of the presence of carotid atherosclerosis (P <0.05). The ROC curve used to identify the diagnostic accuracy of serum Metrnl level in the predication of T2DM subjects with carotid atherosclerosis revealed an area under the curve (AUC) of 0.742. The optimal cut-off value was 0.61 ng/ml with a sensitivity of 77.6% and a specificity of 58.8%.ConclusionsThis cross-sectional study clearly demonstrated that elevated serum Metrnl level was significantly associated with higher risk of the presence of carotid atherosclerosis. Metrnl is a promising therapeutic target for T2DM and its macro-vascular diseases.